2014
DOI: 10.1210/jc.2013-4440
|View full text |Cite
|
Sign up to set email alerts
|

Two Years of Denosumab and Teriparatide Administration in Postmenopausal Women With Osteoporosis (The DATA Extension Study): A Randomized Controlled Trial

Abstract: Two years of concomitant teriparatide and denosumab therapy increases BMD more than therapy with either medication alone and more than has been reported with any current therapy. The combination of these agents may prove to be an important treatment option in patients at high risk of fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(173 citation statements)
references
References 24 publications
7
160
0
4
Order By: Relevance
“…One hundred postmenopausal women with osteoporosis were randomized to receive teriparatide and denosumab, alone or in combination for 12 months. This study showed a densitometric bene fit in year 1 in the combination arm which was sustained in year 2 (43). As anticipated, patients on monotherapy with denosumab showed a decrease in BTMs while patients in the teriparatide alone arm showed an increase of BTMs.…”
Section: Pthsupporting
confidence: 79%
“…One hundred postmenopausal women with osteoporosis were randomized to receive teriparatide and denosumab, alone or in combination for 12 months. This study showed a densitometric bene fit in year 1 in the combination arm which was sustained in year 2 (43). As anticipated, patients on monotherapy with denosumab showed a decrease in BTMs while patients in the teriparatide alone arm showed an increase of BTMs.…”
Section: Pthsupporting
confidence: 79%
“…In patients on prior bisphosphonate, the increase at the total hip was not progressive as there was an early reduction in total hip BMD before the increase in the later months of treatment, particularly in those who were previously treated with alendronate or risedronate (14). Similar continued increases in BMD to 24 months have been reported in other studies (3,(15)(16)(17). Quantitative computed tomography allows the study of bone strength by applying finite element models.…”
supporting
confidence: 82%
“…Bone formation markers increase within days of starting teriparatide and reach a peak between 6 and 12 months. They remain above baseline for the whole of the 24 month treatment period (15,16). The markers even remain elevated in the setting of glucocorticoid-induced osteoporosis (3).…”
Section: Bone Turnover Markersmentioning
confidence: 99%
“…With the de novo combination of TPTD and denosumab, most of the TPTD-induced bone formation is likely to be modeling based because denosumab is such a potent resorption inhibitor, even when combined with TPTD. (47,48) With the de novo combination treatment, both spine and hip BMD increments were larger than observed with either agent alone, and high-resolution peripheral QCT indicated that the TPTD-induced increment in cortical porosity was reduced in the radius and tibia with combination therapy. (49) …”
Section: Cortical Bone Envelopementioning
confidence: 99%